KEWIRAUSAHAAN DALAM PERSPEKTIF ETIKA BISNIS - Pradipta, Gedeon Adinata; Pabayo, Yohanes Theo (Jurnal Pijar, 2024)
Business ethics is an important key in running a business, an inseparable aspect of entrepreneurship. As the importance of corporate social responsibility and its impact on society and the environment increases. Entrepreneurs must understand and apply ethical principles in all aspects of business. Business ethics build consumer trust, good relationships with stakeholders, and a strong company reputation. In entrepreneurship, business ethics encourage moral decisions in determining prices, promotions, treatment of employees, as well as responsibility for the environment and surrounding communities. The application of good business ethics makes entrepreneurship a positive force in creating value, building sustainable relationships, and making positive contributions to society and the environment. This article aims to explain the concept of business ethics from the perspective of entrepreneurship studies, highlight the importance of ethics in business decision making, and provide examples of ethical practices in entrepreneurship.